A Structural Equation Model of Work Engagement Among Public Secondary Schools in Region XII - Gaquit, Marylou (The Future of Education Journal, 2025)
This study aimed to determine the best-fit structural model for work engagement among public secondary teachers in Region XII, Philippines. A descriptive correlational research design was used to attain its objectives. Adapted survey questionnaires consisting of items designed mainly to answer the problems of the study were used. To generate the best-fit model for work engagement, structural equation modeling (SEM) was used. The results revealed that the level of servant leadership was very high, which implied that it was always manifested. The level of organizational culture was high, which implied it was often demonstrated. The level of organizational commitment was high, which implied that it was oftentimes observed. The level of work engagement of teachers was high, which implied that it was oftentimes evident. Further, all of the exogenous variables had positive correlations with work engagement. These showed that as the level of servant leadership, organizational culture, and organizational commitment increased, it resulted in a corresponding increase in the level of work engagement. Moreover, the combined influence of the three exogenous variables in this study on work engagement was significant. The best-fit structural equation model yielded good model results, as indicated by the indices of goodness of fit. It was revealed that there were significant associations between these variables: servant leadership and organizational commitment, servant leadership and organizational culture, and organizational commitment. Also, servant leadership, organizational culture, and organizational commitment were found to have a direct positive influence on work engagement and are significantly associated.